Trustworthly Global Computing 5th International Symposium, TGC 2010, Munich, Germany, February 24-26, 2010, Revised Selected Papers - Wirsing, Martin; Hofmann, Martin; Rauschmayer, Axel.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 5th International Symposium on Trustworthly Global Computing, TGC 2010, held in Munich, Germany, in February 2010. The 17 revised full papers presented and the 7 invited papers were carefully reviewed and selected from 31 submissions. The papers are organized in topical sections on types and processes; games and concurrent systems; certification of correctness; tools and languages; and probabilistic aspects.
Invited Talks -- Symbolic and Analytic Techniques for Resource Analysis of Java Bytecode -- Perspectives in Certificate Translation -- Uniform Labeled Transition Systems for Nondeterministic, Probabilistic, and Stochastic Processes -- Toward a Game-Theoretic Model of Grid Systems -- Functions as Processes: Termination and the -Calculus -- Predicate Encryption for Secure Remote Storage -- Trust in Crowds: Probabilistic Behaviour in Anonymity Protocols -- Types and Processes -- Expressiveness of Generic Process Shape Types -- A Java Inspired Semantics for Transactions in SOC -- Responsive Choice in Mobile Processes -- A Model of Evolvable Components -- Games and Concurrent Systems -- The Impact of Altruism on the Efficiency of Atomic Congestion Games -- Stressed Web Environments as Strategic Games: Risk Profiles and Weltanschauung -- An Algebra of Hierarchical Graphs -- Property-Preserving Refinement of Concurrent Systems -- Certification of Correctness -- Certificate Translation for the Verification of Concurrent Programs -- Certified Result Checking for Polyhedral Analysis of Bytecode Programs -- Tools and Languages -- A Novel Resource-Driven Job Allocation Scheme for Desktop Grid Environments -- A Framework for Rule-Based Dynamic Adaptation -- CarPal: Interconnecting Overlay Networks for a Community-Driven Shared Mobility -- Refactoring Long Running Transactions: A Case Study -- Probabilistic Aspects -- Approximate Model Checking of Stochastic COWS -- Probabilistic Aspects: Checking Security in an Imperfect World -- A Tool for Checking Probabilistic Properties of COWS Services.
Keywords: Computer science; Computer Communication Networks; Software engineering; Data encryption (Computer science).; Coding theory; Computer software; Information Systems; Computer Science; Data Encryption; Computer Communication Networks; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Software Engineering; Coding and Information Theory